Prioritizing dimensions of entrepreneurial ecosystem: A proposed framework - Saeed Mujahid; Shujaat Mubarik; Navaz Naghavi (Journal of Global Entrepreneurship Research, 2019)
The objective of this study is to prioritize the various dimensions of an entrepreneurial ecosystem (EES) and propose a framework for developing it. The study adopted a threefold approach to meet the objective. First, we extracted 63 dimensions of the entrepreneurial ecosystem through a comprehensive literature review. Second, the extracted dimensions were then shortlisted by focusing on the importance of each in the entrepreneurial ecosystem. Thirty-one selected dimensions were grouped in eight core dimensions, namely markets, finance, human resource development, support, government role, infrastructure, industrial network relationship, and mentorship. Third, the study applied the analytical hierarchy process to prioritize the selected dimensions and sub-dimensions of EES. Data was collected from experts using a bi-polar questionnaire. Results of pairwise comparisons reveal that human resource development possessed the highest weight, followed by finance, support, and industrial relationship. Markets emerged as the least important dimension. The proposed EES provides a basic framework that can be replicated in a specific area to identify the industry-related EES framework.
Keywords: 650; Entrepreneurial ecosystem; Business environment; Business support; Analytical hierarchal process